Enhanced photocatalytic hydrogen generation and photostability of ZnO nanoparticles obtained via green synthesis. (23rd February 2017) - Archana, B.; Manjunath, K.; Nagaraju, G.; Chandra Sekhar, K.B.; Kottam, Nagaraju
Abstract: ZnO nanoparticles are prepared by green synthesis using Moringaoleifera natural extract. XRD and Raman analysis show crystalline ZnO with wurtzite structure. SEM and TEM images show the average size of the nanoparticles to be 100–200 nm. Photocatalytic generation of hydrogen by these nanoparticles has been investigated under UV–Visible light irradiation. Na2 S and Na2 SO3 sacrificial agents dispersed with the photocatalyst are employed as hole scavengers. ZnO nanoparticles with smaller size shows better H2 evolution rates up to 360 μmol hg −1 . It is noteworthy that ZnO nanoparticles prepared via novel green synthesis exhibits oxygen vacancies and registers enhanced photocatalytic activity as well as good photostability. Graphical abstract: Highlights: ZnO nanoparticles obtained via green synthesis. The amount of fuel plays a crucial role to get NPs with definite shape, size and properties. ZnO NPs register enhanced H2 evolution activity under UV–vis light. Oxygen vacancies are responsible for the excellent photocatalytic activity. ZnO NPs shows very good photostability.